To solve for x in the equation given, we can start by taking the natural logarithm of both sides:
ln(4^(x-1/2)) = ln(2x^2)
Using the property of logarithms that states ln(a^b) = b*ln(a), we can rewrite the left side of the equation as:
(x-1/2) * ln(4) = 2*ln(2x)
Next, we can simplify this expression by using the fact that ln(4) = ln(2^2) = 2*ln(2):
(x-1/2) * 2*ln(2) = 2*ln(2x)
Now, we can distribute the terms and simplify further:
2x*ln(2) - ln(2) = 2*ln(2x)
2x*ln(2) - ln(2) = 2*ln(2) + 2*ln(x)
2x*ln(2) - ln(2) = ln(4) + ln(x^2)
2x*ln(2) - ln(2) = ln(4x^2)
Now, we can raise both sides as e (base of natural logarithm) to eliminate the logarithms:
e^(2x*ln(2) - ln(2)) = e^(ln(4x^2))
This simplifies to:
e^(2x*ln(2)) * e^(-ln(2)) = 4x^2
Using the property that e^(ln(a)) = a , we get:
2^2x * 1/2 = 4x^2
2^x = 4x^2
Now, we can rewrite this equation as:
2^x = 2^(2x)
Since the bases are the same, we can set the exponents equal to each other:
x = 2x
This simplifies to:
x = 0
Therefore, the solution to the given equation is x = 0.
4^[x-1over2]=2x^2
1 answer